2022
DOI: 10.3389/fmed.2022.773105
|View full text |Cite
|
Sign up to set email alerts
|

Features of Gut Microbiome Associated With Responses to Fecal Microbiota Transplantation for Inflammatory Bowel Disease: A Systematic Review

Abstract: Fecal microbiota transplantation (FMT) has been seen as a novel treatment for inflammatory bowel disease (IBD). The results on microbial alterations and their relationship to treatment efficacy are varied among studies. We performed a systematic review to explore the association between microbial features and therapy outcomes. We searched PubMed, Web of Science, Embase, and Cochrane Library databases from inception to November 2020. Studies that investigated the efficacy of FMT and baseline microbial features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…By November 2020, a systematic review involving 30 randomized controlled trials (RCT) of FMT suggested that uniform and standardized methods were needed for research. [ 75 ] Despite different microbial taxa of donors of responders and non‐responders having been observed, the inconsistent results were due to the different investigating criteria. Such inconsistencies might increase the burden of regulating FMT, leading to varied regulations and ethical considerations among countries.…”
Section: The Development Of Fmtmentioning
confidence: 99%
“…By November 2020, a systematic review involving 30 randomized controlled trials (RCT) of FMT suggested that uniform and standardized methods were needed for research. [ 75 ] Despite different microbial taxa of donors of responders and non‐responders having been observed, the inconsistent results were due to the different investigating criteria. Such inconsistencies might increase the burden of regulating FMT, leading to varied regulations and ethical considerations among countries.…”
Section: The Development Of Fmtmentioning
confidence: 99%